Establishing Line Throughput with Regard to the Operation of Longer Trains - Široký, Jaromír; Široká, Pavlína; Vojtek, Martin; Radek, Divoký (Elsevier Science BV, 2021)
The paper deals with the issue of capacity of railway infrastructure in connection with the operation of freight trains with a length of up to 740 m. First, the facts in the field of the arrangement of railway infrastructure elements that may have a potential impact on capacity will be listed. Subsequently, there will be proposed indicators that can be used for detection of possible changes in capacity, due to the operation of trains with a length of 740 m. In the last phase, several simulation scenarios will be realized in the OpenTrack program. In these scenarios 740 m long trains will be deployed on the selected routes of the model timetable. The simulation results will eventually be evaluated using previously proposed indicators.
Zjišťování propustnosti tratí s ohledem na provoz dlouhých vlaků
Keywords: long train; operation of train; simulation; timetable; dlouhý vlak; provoz vlaku; simulace; jízdní řád